The Effect of Product Quality and Promotion on the Purchase Decision of Proris Syrup at PT. Pharos Indonesia - Kurnia Utami Pasi (CV Raskha Media Group, 2025)
This study investigates the impact of product quality and promotion, both individually and simultaneously, on consumer purchasing decisions for Proris Syrup. The research involved 71 consumers who had previously purchased the product. Data collection was carried out using documentation, interviews, and questionnaires as primary instruments. The analysis techniques applied include multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results of the t-test indicate that product quality and promotion each have a significant influence on consumer purchasing decisions. Furthermore, the F-test results confirm that when combined, both variables jointly have a significant effect on purchasing behavior. The R² value obtained is 0.784, meaning that 55.4% of the variation in consumer purchasing decisions can be explained by product quality and promotion. Meanwhile, the remaining 44.6% is influenced by other factors not examined in this study, such as price, personal preferences, cultural background, brand image, and service quality. Overall, the findings highlight the crucial role of product quality and promotional strategies in shaping consumer purchasing behavior. Companies are therefore encouraged to maintain high product standards and implement effective promotional activities to strengthen customer interest and improve sales performance.